Civil Unions in Italy and Couple Asymmetries - De Rosa, Eugenia; Inglese, Francesca; Napoleone, Vincenzo (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2022)
The approval of the law on Civil Unions (law 20 May 2016 n.76) marked an important step in Italy on the side of institutional and cultural change and the recognition of the rights of LGBT + people with effects also on the cognitive side making it possible to investigate, in a sample or census manner, a specific segment of that population. The aim of this work is to provide a picture of the main socio-demographic characteristics of people in civil union and to carry out initial exploratory analyzes on the existence of any couple asymmetries considering the degree of homogamy / heterogamy between the partners in relation to some indicators of belonging to a group (level of education, occupational status and professional position, territorial mobility and citizenship) as well as the degree of openness and heterogeneity of homosexual couples, of women and men, compared to heterosexual couples.